MULAN'S GREAT UPWARD DRIVE TOWARD ANDROCENTRISM IN MULAN IN DISNEY BELOVED TALES BY JANE BRIERLY, ROBYN BRYANT AND STEPHANIE WERNER - Erna Dwi Listiari; Sutarto Sutarto; Supiastutik Supiastutik (Fakultas Ilmu Budaya Universitas Jember, 2014)
This paper seeks to outline the representation of woman character specifically in using her drive in respondingto androcentrism in Mulan in Disney Beloved Tales. It is one of short stories written by Jane Brierly, RobynBryant and Stephanie Werner and published in 2001 in Canada. The androcentrism undergone by woman maincharacter will be discussed. The great upward drive will be discussed and related to the woman maincharacter's response to androcentrisms. This will be placed in the context of woman representation in literaryworks. The approaches used in this discussion are feminist and psychological approach. Feminist approach isused to know the woman character's position in the story and how she is represented. Psychological approach isused to know the psychological state and the response of the main character toward the androcentrisms in thestory . The method of the study used in this thesis is deductive method from the general discussion to the specificdiscussion. The data are collected through library and cyber research. The result of the research shows thatMulan, the main woman character experiences three kinds of androcentrisms namely woman for reproduction,ethical concept and warfare. She uses her great upward drive in responding the three androcentrisms. Therepresentation of Mulan is made very positively that gives good values about woman character in the literarywork.Keywords: great upward drive, tales, Mulan, feminist critique, androcentrism, patriarchy.